2021
DOI: 10.3390/ijms22031060
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Salicylate Influences the Pseudomonas aeruginosa Biofilm Structure and Susceptibility Towards Silver

Abstract: Hard-to-heal wounds are typically infected with biofilm-producing microorganisms, such as Pseudomonas aeruginosa, which strongly contribute to delayed healing. Due to the global challenge of antimicrobial resistance, alternative treatment strategies are needed. Here, we investigated whether inhibition of quorum sensing (QS) by sodium salicylate in different P. aeruginosa strains (QS-competent, QS-mutant, and chronic wound strains) influences biofilm formation and tolerance to silver. Biofilm formation was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The potential application for QS inhibitors lies not only in the modulation or inhibition of bacterial communication but also in their application alongside traditional treatment methods to potentiate their efficacy. The use of QS inhibitors to potentiate the effect of antimicrobial agents has been previously demonstrated, including sodium salicylate in combination with silver ( Gerner et al, 2021 ) and in combination with antibiotics ( Polonio Roy et al, 2001 ; Brackman et al, 2011 ; Belfield et al, 2017 ), showing increased MBEC susceptibility of S. epidermidis to vancomycin ( Polonio Roy et al, 2001 ). In this study, exposure to 10 mM NaSa resulted in a twofold decrease in the MBEC of rifampicin (from 1,024 to 512 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential application for QS inhibitors lies not only in the modulation or inhibition of bacterial communication but also in their application alongside traditional treatment methods to potentiate their efficacy. The use of QS inhibitors to potentiate the effect of antimicrobial agents has been previously demonstrated, including sodium salicylate in combination with silver ( Gerner et al, 2021 ) and in combination with antibiotics ( Polonio Roy et al, 2001 ; Brackman et al, 2011 ; Belfield et al, 2017 ), showing increased MBEC susceptibility of S. epidermidis to vancomycin ( Polonio Roy et al, 2001 ). In this study, exposure to 10 mM NaSa resulted in a twofold decrease in the MBEC of rifampicin (from 1,024 to 512 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of NaSa on biofilm susceptibility using silver was performed as described previously ( Gerner et al, 2021 ), but S. aureus ATCC 25923 was used to establish a biofilm for 24 h without inclusion of serum. Briefly, semisolid collagen type I gels with 0, 0.1, 1 or 10 mM NaSa were inoculated with 5 μL 10 8 CFU/mL bacteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is, at least partly, related to the lack of appropriate understanding of the biological mechanisms governing the regulation of the immune response to the targeted microorganisms that have been exposed to QS-inhibiting substances. Our research group has previously shown that sodium salicylate (NaSa), the sodium salt of the bioactive metabolite of acetylsalicylic acid (Aspirin®), interferes with P. aeruginosa QS, reducing virulence factor and biofilm production ( Gerner et al., 2020 ; Gerner et al., 2021 ). In this study, we aim to evaluate the effect of NaSa on the ability of P. aeruginosa to modulate immune response processes, such as phagocytosis, immune cell migration, and secretion of cytokines, chemokines, and tissue-degrading enzymes.…”
Section: Introductionmentioning
confidence: 99%